ANALISIS DAMPAK SOSIAL EKONOMI TERHADAP PERMINTAAN ROKOK DI PROVINSI BANTEN - Wawan Hermawan (Jurnal Ekonomi-Qu, 2020)
The increase in cigarette consumption in Banten Province cannot be denied from the number of smokers from a young age. Household characteristics contribute to cigarette consumption, so what is the socio-economic role of cigarette demand in Banten Province. The SUSENAS data of March 2019 became the database for the OLS model used. The results showed the price elasticity of the demand for cigarettes for total cigarettes, the types of SKM, SKT and SPM showed not elastic. Cigarettes are also a normal goods with an income elasticity of less than 1. Age, number of household members and education level have a positive effect on cigarette consumption, except for gender which has a negative effect. Rural area variables have a positive effect, poor category of household has a negative effect and health insurance has a negative effect on cigarette consumption.